S MALL AND MEDIUM SCALE ENTERPRISES MANAGERS' RATING OF SELF-MOTIVATION SKILLS NEEDED FOR BUSINESS SUCCESS IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
The main purpose of the study was to ascertain the small and medium scale enterprisesmanagers'rating ofsivation skills needed for businesssuccess.One research question guidedthe study and one null hypothesis was tested at 0.05 level of significance. Descriptivesurvey research design was adopted and a population of 609 SMEs managers was studiedwithout sampling. A structured questionnaire containing 10 items was face validated bythree experts in the field and used for data collection. Test-retest method was used toestablish the reliability of the instrument. The data analyzed with Pearson ProductMoment Correlation yielded a coefficient of 0.78. Mean and standard deviation were usedto analyze data in respect of the research question while the z-test was used to test thenull hypothesis at 0.05 level of significance. Findings revealed that the respondents ratedself-motivation skills as highly needed for business success in Delta State. Based on thefindings, the researchers concluded that all self-motivation skills are very important forbusiness success. It was, there fore, recommended thatrelevant supervisory and regulatoryagenciesshould organize seminarson self-motivation skills required for effective running ofbusinesses and motivate small and medium enterprise manager to participate. This willhelp to reduce the rate of business failure inDelta State and the country at large.
Keywords: Skills,Entrepreneurship,Entrepreneurialskill,Manager,Self-motivation